Risk Indicators of Tooth Loss Among Mexican Adult Population: A Cross-Sectional Study - Aguilar-Díaz Fatima del Carmen; Borges-Yáñez Socorro Aída; de la Fuente-Hernández Javier (Elsevier, 2021)
Objective: This study aimed to assess the factors associated with tooth loss in an adult population in Guanajuato, Mexico. Methods: This cross-sectional study included individuals enrolled in a community program (2014-2016). Data were gathered through closed-ended questions about sociodemographic characteristics such as sex, age, and schooling. Oral hygiene practices, self-perceived oral health, dental visits during the last 12 months, smoking habits, and diabetes status of the participants were also recorded. A clinical evaluation was performed for each person to register decayed, missing, and filled teeth (DMF-t). Descriptive statistics, bivariate analysis, and negative binomial models were used to identify variables associated with the number of missing teeth. Results: A total of 1640 persons were included in the study. The mean age was 41.6 (±15.4) years; 63.6% were female; and 52.7% had at least 1 missing tooth, with a mean of 2.9 (+4.6) missing teeth. The mean number of missing teeth increased by 5% per year relative to age. Females (relative ratio [RR] = 1.40), smokers (RR = 1.56), people with diabetes who smoke (RR = 3.62), and people who rated their oral health as fair or poor (RR = 1.2) had higher mean values of missing teeth. In contrast, individuals who achieved a high school degree (or above) (RR = 0.81), practiced daily toothbrushing (RR = 0.63), or practiced regular toothbrushing and flossing (RR = 0.65) had fewer missing teeth. Conclusions: More than half of the population has at least 1 missing tooth. The number of missing teeth is higher in individuals with diabetes and unhealthy habits such as smoking. Good oral hygiene practices play an essential role in preventing tooth loss.